Gender and Microfinance in the United Arab Emirates: An Exploratory Review of Concepts and Policy Issues - Akin Fadahunsi; Lana Barake (Journal of Management Practices, Humanities and Social Sciences, 2018)
The objective of this research is to investigate the environment in which microfinance is accessed and administered within the United Arab Emirates to groups of female entrepreneurs. As a corollary to this broad objective, the present paper derives two aims of its own: First, it overviews the literature on the institutional context for microfinance in the UAE with a view to synthesizing the deployment approaches for microfinance programs in the UAE. Secondly, it surveys existing literature on the impact of the administration of microfinance programs on women's entrepreneurial motivation and activities in the UAE. This study is qualitative in nature. Data for current study is retrived from secondary sources such as journal articles, periodicals, books and websites. The paper concludes with remarks that highlight the distinctiveness of the impact of gender on microfinance in the UAE with respect to lending methods, loan sizes, repayment levels and subsequent enterprise performance. The findings indicate that by removing the explicit barriers that obstruct the growth of the region's female entrepreneurs, regional governments have an opportunity to fast track an effective transition to having more sustainable economies.